2010
DOI: 10.1111/j.1365-2362.2010.02312.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of the Paget’s disease of bone: concerns on the introduction of DNA‐based tests in the clinical practice. Advantages and disadvantages of its application

Abstract: Background A large amount of genetic studies have clearly demonstrated the existence of a genetic susceptibility to Paget's disease of bone (PDB). Although the disease is genetically heterogeneous, the SQSTM1 ⁄ p62 gene, encoding a protein with a pathophysiological role in both osteoclast differentiation and activity, has been found worldwide to harbour germline mutations in most of the PDB patients from geographically distant populations originating from different areas of Europe, both in sporadic and familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 103 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…To date, the etiology of the disease is still unclear, and both environmental factors and genetic susceptibility are thought to be involved 22. The disease is characterized by focal increase of bone remodeling and disorganization of normal lamellar structure of the tissue, with consequent susceptibility to bone fractures, pain, and deformities.…”
Section: Clinical Use Of Neridronatementioning
confidence: 99%
“…To date, the etiology of the disease is still unclear, and both environmental factors and genetic susceptibility are thought to be involved 22. The disease is characterized by focal increase of bone remodeling and disorganization of normal lamellar structure of the tissue, with consequent susceptibility to bone fractures, pain, and deformities.…”
Section: Clinical Use Of Neridronatementioning
confidence: 99%
“…Therefore, from a practical point of view, even in the lack of specific comparative studies among the different diagnostic tools, it can reasonably be suggested that all first-degree relatives of pagetic patients should in any case undergo a periodic screening of at least t-ALP (or other bone turnover markers), generally starting from 40 years of age, or earlier if the affected relative had an onset of the disease at an even earlier age. This will make possible to carry out adequate surveillance and to identify early the presence of PDB (especially polyostotic forms), hopefully still in a pre-/asymptomatic form, and thus establish any appropriate therapy in order to prevent disease progression [ 51 ]. In fact, the assessment of t-ALP appears as the simplest, largely available, cheapest, appropriate, and thus cost-effective tool as compared to the measurement of other bone turnover markers, or the use of X-rays and bone scan.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Moreover, ZNF687 mutations have been associated to a particularly increased risk of neoplastic degeneration in GCT, while either GCTs or osteosarcomas have been often described in the pedigrees with PFN1 mutation [ 14 , 56 , 57 ]. To date, specific guidelines addressing when and why perform genetic screening in PDB are still lacking and certainly additional information is required to address whether genetic testing may have a good cost–benefit ratio for all PDB patients [ 51 ]. However, based on the available clinical information, we suggest that genetic screening could be performed in familial PDB cases and in all PDB patients with early onset (< 50 years), polyostotic PDB.…”
Section: Results and Recommendationsmentioning
confidence: 99%